STUDY OF SILICA SCALE CHARACTERISTICS AND ITS MECHANISM IN PAD 30 CANAL SYSTEM, DIENG GEOTHERMAL FIELD - Rahat Prabowo, Teguh
High intensity occurance of silica scale has become one of the main problems in Dieng Geothermal Field. The existence of silica scale can clog the brine flow in surface facilities such as canal system and can result in decrease of reinjection flowrate. No detailed study regarding silica scale characteristics in Dieng Geothermal Field has been published until today. This research was meant to study the physical, chemical, and mineralogical characteristics of silica scale deposited in Pad 30 canal system, to estimate its deposition mechanism, and the factors involved in the deposition process. The result of this study can be used for proposing the effective solution of silica scale in Pad 30 canal system. This study was conducted using field observation method (physical characeristics), XRF method (chemical characteristics), XRF and petrography method (mineralogy characteristics). The scale has physical characteristics of solid, not very adhesive, soft, has rough texture, porous, and some of the silica scale has layered structures with different colours. XRF analysis showed that the scale has heavy metal elements which have potential to contaminate the environment, such as As, Pb, and Sb. XRD analysis showed that the silca scale has amorphous phase and doesn’t has any silica in crystal forms, such as quartz, crystobalite, and chalcedony. SEM analysis showed that the silica particle size has range between 10 – 35 ?m. Deposition mechanism was obtained from comparison between the scale physical characteristics and SEM analysis with previous researches used as literatures in this study. Analysis showed that the deposition mechanism is homogenous mechanism. Deposition process is controlled by several factors such as temperature, brine flowrate, and pH value. Amorphous silica scale was increased in numbers when the temperature decrease, low flowrate, and more neutral pH. Brine chemical composition also controlling the silica scale chemical composition. Amorphous silica scale formed in Pad 30 can be classified as solid waste. The mitigation methods that have been conducted in Pad 30 such as canal system, pond, and waterfall system need to be monitored carefully so that no heavy metals contamination from the silica scale into the environment, especially soil and vegetations.